Piloting ‘Clever Kids’: A randomized-controlled trial assessing feasibility, efficacy, and acceptability of a socioemotional well-being programme for children with dyslexia - Boyes, Mark; Leitão, S.; Claessen, Mary; Dzidic, Peta; Badcock, N.A.; Nayton, M. (WILEY, 2021)
Children with dyslexia are at elevated risk of internalizing (emotional) and externalizing (behavioural) problems. Clever Kids is a nine-week socioemotional well-being programme developed specifically for upper primary school children with dyslexia. In a small randomized-controlled trial, we tested the feasibility, efficacy, and acceptability of the Clever Kids programme. ‘Forty children (Mage = 10.45 years, 65% male) with clinically diagnosed dyslexia too part in the study. Children were randomized to either attend Clever Kids (n = 20) or to a wait-list control condition (n = 20). Coping skills, self-esteem, resilience, emotion regulation, and internalizing and externalizing symptoms were measured at pre-programme, post-programme, and at three-month follow-up. Recruitment and retention rates indicate high feasibility for further evaluation of the programme. There was a significant interaction between intervention condition and time for non-productive coping [F(2, 76) = 4.29, p = 0.017, f2 = 0.11]. Children who attended Clever Kids significantly reduced their use of non-productive coping strategies, and this was maintained at three-month follow-up assessment. For all other outcomes, the interactions between intervention condition and time were non-significant. The programme appears acceptable to children with dyslexia and their families, but may be improved by further reducing the number of activities involving reading and writing. Clever Kids improved the coping skills of children with dyslexia; however, a larger trial is needed to replicate this finding and investigate whether programme attendance is associated with additional improvements in children’s socioemotional well-being.